As representações sociais da língua portuguesa em uma situação plurilíngue concorrencial no Timor-Leste - Souza, Lucimar França dos Santos (2017)
The objective of this work is to investigate how the Portuguese Language (LP) is represented in TimorLeste, considering the plurilingual context in which it is inserted. From this perspective, the research involved 16 East Timorese teachers, whose basic formation occurred in the period of Indonesian domination. The problem of the research is the social representations of LP in East Timorese imagery. Through interviews, narratives, questionnaires and interviews, based on Gil (1999) and Marconi and Lakatos (1990), I tried to analyze the subjects' perceptions regarding the officialisation of LP in East Timor, as well as the dynamics of that language in contact with the local languages, among them, the Tetun that has the status of national language and also official language. The study is linked to the field of Sociolinguistics, based on the assumptions of Calvet (2002, 2007), regarding the analysis of linguistic policies (PL) at the governmental level and, considering Article 13, item 1, of the Constitution (C-RDTL / 2002), Decree no. 14 of the Law on Bases and Education (LBE / 2008) and Decree No. 23 of the Civil Service Commission (CFP / 2009), whose texts consecrate LP as official, Of the civil service, respectively. Article 13 also includes, in item 2, the valorization of the national language and local languages. In view of this, we ask ourselves: what are the representations of LP in the East Timorese imaginary? The results show that teachers are willing to accept the reinsertion of LP based on their recent official status and aim at a linguistic planning appropriate to the real needs of the East Timorese State reconstruction process. We hope that the questions raised will broaden the already existing discussions on the subject and will reveal other important aspects about the management of languages in sociolinguistically complex contexts, such as the East Timorese State. On the basis of empirical material, we affirm that the East Timorese State has sovereign management over the status of languages